Multivalent Exosome Based Protein Vaccine: A “Mix and Match” Approach to Epidemic Viruses’ Challenges - Mafalda Cacciottolo; Li-En Hsieh; Yujia Li; Michael J. LeClaire; Ciana L. Mora; Christy Lau; Charles Dwyer; Kristi Elliott; Minghao Sun (Vaccines)
Background: Endemic viruses are becoming increasingly the norm, and the development of a rapid and effective vaccine is necessary. Methods: Here, we used our StealthXTM exosome platform to express either Influenza H3 (StealthXTM-Hemagglutinin, STX-H3), SARS-CoV-2 Delta spike (StealthXTM-Spike, STX-S) or respiratory syncytial virus proteins (StealthXTM-RSV fusion protein, STX-RSV) protein on the membrane surface and facilitate their trafficking to the exosomes. Results: The administration of exosomes carrying one of the antigens by themselves resulted in a strong immune response with the production of a potent humoral and cellular immune response in mice. Interestingly, these effects were obtained with the administration of nanograms of protein and without adjuvant. We tested the possibility of manufacturing a multivalent vaccine by combining exosomes expressing either STX-H3, STX-RSV or STX-S exosomes in the same formulation, in a “mix and match” approach. Mice immunized with the cocktail vaccine showed an increased immune response against all three antigens received. Conclusions: The results further demonstrated that our STX trivalent cocktail vaccine elicited a strong immune response, and the magnitude of the responses was comparable to the single antigen administered individually. Our data show that our exosome platform has enormous potential to revolutionize vaccinology by rapidly facilitating antigen presentation, to tackle the fast-evolving viral infections.